Hierarchical clustering reveals unique features in the diel dynamics of metabolites in the CAM orchid Phalaenopsis. (11th April 2019) - Ceusters, Nathalie; Luca, Stijn; Feil, Regina; Claes, Johan E; Lunn, John E; Van den Ende, Wim; Ceusters, Johan
Abstract : Hierarchical agglomerative clustering of diel metabolite data from photosynthetic and central C-metabolism in the CAM plant Phalaenopsis 'Edessa' reveals consistencies and marked differences in carbon and energy homeostasis in CAM and C3 plants. Abstract: Crassulacean acid metabolism (CAM) is a major adaptation of photosynthesis that involves temporally separated phases of CO2 fixation and accumulation of organic acids at night, followed by decarboxylation and refixation of CO2 by the classical C3 pathway during the day. Transitory reserves such as soluble sugars or starch are degraded at night to provide the phospho enol pyruvate (PEP) and energy needed for initial carboxylation by PEP carboxylase. The primary photosynthetic pathways in CAM species are well known, but their integration with other pathways of central C metabolism during different phases of the diel light–dark cycle is poorly understood. Gas exchange was measured in leaves of the CAM orchid Phalaenopsis 'Edessa' and leaves were sampled every 2 h during a complete 12-h light–12-h dark cycle for metabolite analysis. A hierarchical agglomerative clustering approach was employed to explore the diel dynamics and relationships of metabolites in this CAM species, and compare these with those in model C3 species. High levels of 3-phosphoglycerate (3PGA) in the light activated ADP-glucose pyrophosphorylase, thereby enhancing production of ADP-glucose, the substrate for starch synthesis. Trehalose 6-phosphate (T6P), a sugar signalling metabolite, was also correlated with ADP-glucose, 3PGA and PEP, but not sucrose, over the diel cycle. Whether or not this indicates a different function of T6P in CAM plants is discussed. T6P levels were low at night, suggesting that starch degradation is regulated primarily by circadian clock-dependent mechanisms. During the lag in starch degradation at dusk, carbon and energy could be supplied by rapid consumption of a large pool of aconitate that accumulates in the light. Our study showed similarities in the diel dynamics and relationships between many photosynthetic metabolites in CAM and C3 plants, but also revealed some major differences reflecting the specialized metabolic fluxes in CAM plants, especially during light–dark transitions and at night.